Comparison of chemical and molecular characteristics of Phyllanthus amarus and Phyllanthus urinaria species - Huynh Thi Thu Hue,; Le Tat Thanh,; Do Thi Thanh Trung,; Nguyen Thị Bich Ngoc, (Vietnam Journal of Science and Technology, 2025)
Phyllanthus amarus and Phyllanthus urinaria belonging to Phyllanthaceae are the well-studied for their precious extracted compounds. Phyllanthin and hypophyllanthin provide a variety of potential health benefits for humans.  Phyllanthin and hypophyllanthin biosynthesis pathway is different between P. amarus and P. urinaria.  In our study, with High-performance liquid chromatography (HPLC) to quantify hypophyllanthin and phyllanthin concentration extracted from leaf and stem tissue of these two species showed the concentration of these compounds significantly varied between P. amarus .TN and P. urinaria .TN. Combine with quantitative PCR (qRT-PCR) used for measure expression of six genes that related to the biosynthesis pathway showed the expression of these genes were stronger in P. amarus than P. urinaria. DNA barcoding markers are also used for divergence analysis and phylogenetic construction. Thereby, ITS sequence was expected to be one of standard DNA barcoding markers due to its high conserved site percentage for variations analysis and phylogenetic construction.